Preoperative evaluation for epilepsy surgery: Process improvement - Drees, Cornelia (Neurol Clin Pract, 2017)
BACKGROUND: Epilepsy surgery (ES) can improve seizure outcome. A prolonged duration of presurgical evaluation contributes to epilepsy-related morbidity and mortality. We introduced process changes to decrease evaluation time (ET) and increase ES numbers (excluding vagus nerve stimulation). METHODS: The University of Colorado Hospital patient database was searched for ESs between January 2009 and May 2016. Measures to reduce ET included (1) increasing patient care conference (PCC) frequency; (2) faster intracarotid amobarbital test (IAT) scheduling; (3) dedicated ES clinic; and (4) adding a nurse navigator. ET from noninvasive video-EEG monitoring (P1) to IAT, PCC, and ES, and ES volume were determined and compared for a baseline group (P1 January 2009–March 2013) and a group exposed to process changes (P1 after March 2013), the postchanges group, to assess the effect of these measures. RESULTS: ES number was 61 for the baseline group and 77 for the postchanges group, increasing the annual rate at 3 years after changes from 14.4 to 36.8 (p = 0.0008; 37% yearly increase postchanges). Interventions lowered average ET by 96 days (p ≤ 0.0001), P1 to IAT by 39 days (p = 0.0011), and P1 to PCC by 58 days (p = 0.0002). CONCLUSIONS: Simple process changes, including more frequent patient care conferences, faster scheduling, a dedicated ES clinic, and a nurse navigator significantly decreased evaluation times and increased ES numbers. Centers could utilize similar strategies to improve process and surgical volume and thereby increase patient seizure control and safety.